(untitled) (SAARC Journal of Agriculture, 2020)
Five advanced potato genotypes, along with three check varieties were evaluated at six locations in order to find out the stable varieties for commercial cultivation in Bangladesh. Combined analysis exhibited a highly significant variability among the genotypes, locations and GEI. The average tuber yield at 90 days after planting (DAP) of the genotypes ranged from 31.18 t ha-1 in the check BARI Alu-28 to 43.8 t ha-1 in the clone 9.35. The result of AMMI analysis of tuber yield at 90 DAP also showed that the first IPCA1 captured 55.30% of the interaction SS. IPCA2, IPCA3 and IPCA4 explained 29.01, 8.55 and 7.08% of GE interaction SS, respectively. In general, the AMMI2 model contained 99.94% of the treatment SS, while the residual contained 0.06%. In ASV method, the clone 9.125, followed by the check BARI Alu-28 and clone 9.91 were more stable than 9.35. Biplot of IPCA1 and IPCA2 covers 84.3% of GE interaction. Biplot analysis also showed that clone 9.44 and 9.35 and the environment of Gazipur and Jashore had a better result in the GE interaction. Clone 9.44 had specific adaptation with the environment of Gazipur and Jashore, while 9.35 had specific adaptation with Gazipur and Jamalpur. Clone 9.125, 9.91, BARI Alu-28, BARI Alu-8 and clone 9.112 were located toward the center of the biplot and can be considered as stable. Based on the GSI the most desirable genotype for both stability and high tuber yield is the clone 9.125 followed by clones 9.112, 9.91 and 9.35. SAARC J. Agri., 18(1): 73-86 (2020)